Factors associated with stunting in under-five children with environmental enteropathy in slum areas of Jimma town, Ethiopia - Regassa, Rediet; Belachew, Tefera; Duguma, Markos; Tamiru, Dessalegn (Frontiers in Nutrition, 2024)
Abstract Introduction: Stunting is a major public health issue with a significant influence on the health and development of children in low-income countries, where it affects up to 32% of children. Nutritional intake is impacted by alterations in intestinal permeability and underlying chronic inflammation, which hinders children's normal linear growth. Environmental enteropathy is a poorly understood condition with chronic intestinal inflammation. The purpose of this study was to identify the magnitude of stunting, change in growth, and factors associated with stunting and change in height for the age Z score of children with an elevated lactulose-to-mannitol ratio. Methods: An observational follow-up study was conducted to follow children with an elevated lactulose-mannitol ratio for changes in their linear growth. A lactulose-mannitol test was performed to identify children with elevated lactulose-to-mannitol ratios, indicative of environmental enteropathy. After a one-year follow-up, anthropometry was repeated to assess their linear growth. A multivariable logistic regression analysis was performed to identify independent predictors for stunting in children with elevated lactulose-to-mannitol ratios. All tests were two-sided, and p<0.05 was considered significant. Results: The prevalence of stunting in children with an elevated L: M at baseline and end line were found to be 72.4% (95% CI: 60.3, 84.5) and 78.4% (95% CI: 66.7, 90.2), respectively. In multivariate analysis, a low dietary diversity score (<4 food groups), flies and insects in the toilet area, poor hand washing practices during a critical time, and MUAC z <-2 were significantly associated with stunting. Flies and insects in the toilet area and unsafe disposal of feces were significantly associated with changes in HAZ in children with elevated lactulose-to-mannitol ratios, an indicator of environmental enteropathy. Conclusion: Most of the children with an elevated lactulose-to-mannitol ratio in the study population were stunted, and no significant change in their linear growth was observed after a one-year follow-up. Therefore, further investigation and urgent intervention are needed to prevent environmental enteropathy and stunting among under-five children in this community who are exposed to very poor sanitary conditions and other risk factors for malnutrition.